Collective Decision Making in Rural Japan (1984)
The origins of this study of rural Japanese decision making lie in my nearly simultaneous discoveries of Niwa Fumio's fine novel of rural passion and intrigue, The Buddha Tree, and the transactional analysis of social relations and organiza- tions, or, as it is sometimes called, social exchange theory, which was made especially prominent in political science by Olson (1956), in sociology by Blau (1964), and in anthropology by Barth (1966). Thus, this is a book written with two rather disparate audiences in mind, readers interested primarily in exchange and decision-making phenomena, on the one hand, and readers interested primarily in the unity of experience represented by the Japanese sensibility, on the other.